REGIONAL PRICE SITUATION FOR SUNFLOWER IN ROMANIA (2014-2018) - Radu Lucian PÂNZARU; Dragoș Mihai MEDELETE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper addresses an essential aspect, related to the economic efficiency of sunflower production, i.e. the selling price (lei/kg). This situation is determined by the multiple possibilities for the recovery of sunflower seeds, depending on which producers can negotiate different levels of the selling price on the basis of the quantitative and qualitative parameters of the seeds, which may be stipulated in the recovery contracts or which may be taken into account at the time of sale on the open market, to various beneficiaries. It should be noted that Romania is the main grower and producer of sunflowers in the European Union (about 24% of the total area harvested and about 25% of total production respectively). Addressing the subject, aimed to highlight the differences between the 8 development regions existing at national level, in Romania. The price is characterized by a multiannual national average of 1.39 lei/kg, with limits of 0.99 lei/kg for the West Region in 2014 and 1.61 lei/kg for the South Muntenia Region at the level of 2016. If we look at the indicator in the light of its evolution over time, we see the existence of fluctuating trends.